Methods for Studying the Structure of Social Representations: A Critical Review and Agenda for Future Research. (5th October 2016) - Lo Monaco, Grégory; Piermattéo, Anthony; Rateau, Patrick; Tavani, Jean Louis
Abstract: This article deals with the methodologies commonly used in the framework of the structural approach to social representations. It concerns free and hierarchical evocations, the characterization questionnaire, the similarity analysis, the basic cognitive schemes model, the attribute‐challenge technique and the test of context independence. More than a simple review of these methodologies, it offers a critical approach concerning the problems encountered and related to: thresholds or "cutoff points" used to diagnose the structure (core vs. periphery) and the accuracy of the structural diagnosis, grouping methods employed to reduce the corpus of verbal associations, the dilemma between reliability and feasibility, especially in field research, the adequacy and number of modalities of response in the framework of the structural diagnosis. Following this evaluation, this article suggests potential solutions to overcome these methodological limitations. Moreover, as methodological issues are closely related to theoretical questions, the link between social representation theory and identity approaches is discussed.